Revenue and Distributional Impact Analysis of Indonesian Personal Income Tax Reform in 2008 - Bimo Wijayanto; Yogi Vidyattama (Economics and Finance in Indonesia, 2017)
Since 1983, Indonesian tax policy has been the subject of ongoing reforms in order to replace the old colonial tax arrangements, reduce income dependency from oil and gas, decrease the government's foreign debt and maintain its fiscal sustainability. Nevertheless, after 25 years of reform, actual Indonesian tax performance is still far from what might have been expected as Indonesia have one of the lowest total tax ratios among the ASEAN countries. This research show that the most recent changes put in place may have reduced potential tax revenue from personal income but an increase in the compliance rate.